The Gospel according to Matthew: a commentary - Konradt, Matthias (Baylor University Press, 2020)
"An exegesis of Matthew focusing on scriptural and cultural influences that shaped the narrative of Jesus the Christ"--
Originally published in German in Göttingen: Vandenhoeck & Ruprecht, 2015
Includes bibliographical references
Keywords: Bible -- Matthew -- Commentaries; Kommentar; Bibel / Matthäusevangelium